Prevalence of diabetes mellitus and its relation to diet and physical work in Azad Jammu and Kashmir - Ahmad Danish, Fayaz; Khan, Alam; Khattak, Muhammad Muzaffar Ali Khan (Asian Network for Scientific Information, 2002)
The prevalence of diabetes mellitus and its relation to diet and physical work was studied in three selected districts namely Muzaffarabad, Bagh and Poonch of Azad Jammu and Kashmir. A city, a town and a village were selected from each selected district, and hundred households (families) from each city, town and village were randomly selected for the study. A total 900 households were selected for interview. A responsible individual of 40 years or older of each household was interviewed and information about diabetes, occupation and diet were recorded in the questionnaire. The mean prevalence of diabetes mellitus was 0.95% in the selected region of the state. The prevalence of the disease was higher in cities than towns and villages. The disease was slightly higher in males than females. The milk and meat consumption of the residents of the area was lower than the recommended amount. The exercise level/physical work status of majority of the residents was almost equal to heavy exercise level. The data suggest that at present, the prevalence of diabetes is not of great concern in Azad Jammu and Kashmir. The prevalence of the disease is linked with diet and exercise level/physical work. The residents have marginal deficiency of food intake.